Three-Dimensional Trunk and Lower Limbs Characteristics during Gait in Patients with Huntington's Disease - Mirek, Elzbieta; Filip, Magdalena; Chwała, Wiesław; Banaszkiewicz, Krzysztof; Rudzinska-Bar, Monika; Szymura, Jadwiga; Pasiut, Szymon; Szczudlik, Andrzej (Frontiers in Neuroscience, 2017)
Objective: A number of studies on gait disturbances have been conducted, however, no clear pattern of gait disorders was described The aim of the study was to characterize the gait pattern in HD patients by conducting analysis of mean angular movement changes the lower limb joints and trunk (kinematics parameters). Methods: The study group consisted of 30 patients with HD (17 women and 13 men). The reference data include the results of 30 healthy subjects (17 women and 13 men). Registration of gait with the Vicon 250 system was performed using passive markers attached to specific anthropometric points directly on the skin, based on the Golem biomechanical model (Oxford Metrics Ltd.). The research group and the control group were tested once. Results:Statistically significant (p<0.05) angular changes in gait cycle for HD patients were observed in: insufficient plantar flexion during Loading Response and Pre-swing phases; insufficient flexion of the knee joint during Initial Swing and Mid Swing phases; excessive flexion of the hip in Terminal Stance and Pre-Swing phases and over-normative forward inclination of the trunk in all gait phases. It should be noted that the group of patients with HD obtained, for all the mean angular movement changes higher standard deviation. Conclusion: A characteristic gait disorder common to all patients with HD occurring throughout the whole duration of the gait cycle is a pathological anterior tilt of the trunk. The results will significantly contribute to programming physiotherapy for people with HD, aimed at stabilizing the trunk in a position of extension during gait.